The Effect of Work Environment and Leadership Style on Employee Performance at PT. Kereta Api Logistik in Surabaya - Muhammad Bahrurrozi Romadhoni; Hermien Tridayanti; Helen Pramudita (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
Management is a process or framework that involves guiding and directing a group of people toward organizational goals for tangible purposes. This research will focus more on human resource management, where this management is managing people. The variables to be studied are the work environment (X1), leadership style (X2) and employee performance (Y). The purpose of this study was to analyze the effect of work environment and leadership style variables on employee performance either partially or simultaneously. This research uses a quantitative approach, namely research that in the process uses data in the form of numbers. Respondents in this study were employees of PT. Kereta Api Logistik Surabaya conducted 95 people by conducting a distribution questionnaire and using a saturated sample. The results of the questionnaire were processed using the Multiple Linear Regression Analysis technique using the SPSS program. The results of this study indicate that the variables of Work Environment and Leadership Style have a significant effect both partially and simultaneously on Employee Performance at PT. Kereta Api Logistik Surabaya.